2010
DOI: 10.1590/s1984-46702010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Meso and microhabitat analysis and feeding habits of small nektonic characins (Teleostei: Characiformes) in Neotropical streams

Abstract: The habitat use and feeding habits of a set of nektonic fish species often found in small low-gradient streams in Brazil were investigated. The core species in the present study was Knodus moenkhausii (Eigenmann & Kennedy, 1903), the most abundant of five species in the nektonic guild. Records of the species in 22 streams indicate that K. moenkhausii is associated, on a mesohabitat scale, with runs, and on a microhabitat scale, with sandy bottoms, intermediate depth, and open sites without coverage or submerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
(29 reference statements)
0
13
1
1
Order By: Relevance
“…Species from this group are often dominant in Neotropical streams (Castro, 1999) and were well represented in our streams, except in one of the deforested streams (D2), possibly due to higher water flow and the reduced availability of macrophyte-free space in the water column. Group 6 species are known for their trophic plasticity and opportunism and are capable of successfully using available resources, even in degraded environments (Melo et al, 2004;Ceneviva-Bastos et al, 2010) -which may explain their low sensitivity to deforestation.…”
Section: Discussionmentioning
confidence: 99%
“…Species from this group are often dominant in Neotropical streams (Castro, 1999) and were well represented in our streams, except in one of the deforested streams (D2), possibly due to higher water flow and the reduced availability of macrophyte-free space in the water column. Group 6 species are known for their trophic plasticity and opportunism and are capable of successfully using available resources, even in degraded environments (Melo et al, 2004;Ceneviva-Bastos et al, 2010) -which may explain their low sensitivity to deforestation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a strategy of M. eleotrioides to avoid competition. For other characins a partition of foraging patches has been described as a mechanism that might relieve interspecific competition (Ceneviva-Bastos et al 2010 (Malabarba et al 2013). Further research is needed, however, to corroborate our assumptions.…”
Section: Fsh Communities In Three Floodplain Lakes Of Orinoco Rivermentioning
confidence: 99%
“…Astyanax taeniatus, as well as many other Astyanax species (Uieda, 1984;Abilhoa et al, 2008), also selected slow to moderate water velocities with bedrock and sandy bottoms. Ceneviva-Bastos et al (2010) observed two Astyanax species associated with sandy bottoms. These patterns of habitat use could be reflecting the feeding tactics frequently described for Astyanax species that forage in the water column, feeding on drift items available throughout the year in these coastal streams (Motta, 1988;Motta et al, 1995;Casatti & Castro, 2006;Gibran, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…specific behaviors of fish of different ages. Nonetheless, the study site contained all the mesohabitats frequently found in many rain forest streams from the Mata Atlântica (Mazzoni et al, 2011), including a combination of depths, water velocities and substrata, which represented pools, runs, and riffles, creating conditions suitable for high species diversity (Angermeier & Schlosser, 1989;Ceneviva-Bastos et al, 2010). Depths below 30 cm were avoided by the studied species; this is a typical behavior of mid-water pelagic fish (Costa, 1987;Casatti, 2002;Fogaça et al, 2003;Abilhoa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation